«Կանոնագիրք Հայոց» ժողովածուի խմբագրությունները (Ը. դարի երկրորդ կես-ԺԱ. դարի երկրորդ կես) - Նարինե Վարդանյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
«Армянская книга канонов» составленная Католикосом Ованнесом Одзнеци (717-728) в середине 8-го века была многократно отредактирована и постепенно расширена путем включения новых групп канонов. Ввиду отсутствия более ранних исторических свидетельств или данных рукописей, развитие этого сборника может быть прослежено лишь в общих очертаниях. Тhe “Armenian Book of Canons” to be first compiled by Catholicos Hovhannnes Odznetsi (717-728) in the 8th century was later re-edited and gradually expanded many times including new groups of canons. Due to the lack of historical evidence or earlier manuscript data the development of this collection may be outlined only in general detail.
Keywords: Armenian church; Christianity; Political Science; General legislative and executive papers